‘Peace, Peace When there is No Peace’: The Impact of Prosperity Gospel on Suicide Rate among Nigerian Youth - Uroko, Favour C. (Perichoresis, 2023)
This study examines how the prosperity gospel has led to an increase in suicide cases in Nigeria. Existing literature has established links between the prosperity gospel and exploitation of the poor, but finding literature that establishes links between the prosperity gospel and suicide is difficult to find. The prosperity gospel preys upon the poor and leads people into suicidal desires for lack of wealth. In Nigeria, the church has consistently continued to base its preaching on prosperity. When congregants see that the promise of provision that the church has been laying emphasis upon is not materializing, they resolve to find any means of ending the controversy. Findings reveal that some of the aphorisms of the Nigerian clergymen include “By next week, month, or year, you shall receive a miracle”, “poverty is a curse”, “I can never be poor”, and “givers never lack.” These aphorisms have made the church members expectant of God’s blessing, and when their poor condition continues, they decide to take their life. In Nigeria, the majority of those who commit suicide have experienced a number of stressful life events in the three months prior to their suicide. This study adopted content and documentary analysis as its research methodology.
free